HUBUNGAN PENGETAHUAN DENGAN SIKAP IBU NIFAS TENTANG KUNJUNGAN NIFAS PADA MASA PANDEMI COVID 19 DI KELURAHAN TJ. GUSTA KEC. MEDAN HELVETIA - FATWIANY .; NAILATUN NADRAH (LP2MTBM MAKARIOZ, 2020)
The high maternal mortality rate (AKI) is still not resolved properly because AKI in 2018 is still high at 305/100,000 live births,maternal deaths often occur during nifas. To overcome AKI during nifas period one of them by visiting nifas. One of theaffecting factors is knowledge. The covid-19 pandemic that hit the entire country affected nifas's visit to the Health ministry.The purpose of this study is to analyze the relationship of nifas mother's knowledge with attitudes about nifas visits duringthe covid-19 pandemic. The design of this study is cross sectional with analytical surveys. The study sample was 38 in April-May 2019. Sampling technique is total sampling. Analyze the data using the chi-square statistic test. The results found thatout of 15 people (39.5%) who have a bad attitude there are 9 people (81.8%) have less knowledge about nifas visits duringthe covid-19 pandemic. And of the 23 people who have a good attitude there are 14 people (87.5%) who have sufficientknowledge with a value of p 0.001 then can be interpreted that there is a significant relationship between knowledge and theattitude of the mother nifas about nifas visits during the covid-19 pandemic. Recommendations to improve the socialism ofnifas visits during covid-19.